“Judging Shepherd of Thy Sheep”: Christ and the Role of Mercy in the Dies Irae - Monaco, John A. (Lumen et Vita, 2017)
The 13th century Latin hymn, Dies Irae, is one of the better-known Roman Catholic liturgical sequences, famous for its seemingly-dark portrayal of the Day of Judgment (“Day of Wrath”). Once a staple element of the Requiem Mass, this text has now been relegated to relative obscurity, finding life only in concert halls, where grandiose musical settings of Mozart’s & Verdi’s “Requiem Mass” are performed. In its absence, the Dies Irae is now synonymous with a bleak, medieval theology fixated on death and judgement. However, upon deeper examination, it seems that the “Day of Wrath” can also be read as a “Day of Mercy.” Sorrow for past transgressions and preoccupation with eternal hell constitute only one element of the hymn. Far from being focused on sin and death, the Dies Irae also establishes the vital connection between Christ’s mercy for sinners and the mercy each Christian is called to share with one another. This is seen through the numerous Scriptural allusions which fill the hymn, including those referencing that ‘final day’, when Christ is said to “judge the living and the dead.” In pleading to be on the right side during the separation between the metaphorical “sheep and goats,” the author acknowledges the significance of Christ and His command to love the “least of these” on the Day of Judgement (Matthew 25:40). The Dies Irae contains both a call for mercy and a call to mercy, the latter of which distinguishes itself as the litmus test of salvation.